Improving student's learning activity in PKn learning using picture and picture model in class IV SDN 01 Pancung Soal Pesisir Selatan - Reinita Reinita (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
This research is motivated by the low level of Civics learning activities in grade IV SDN 01 Pancung Problem Pesisir Selatan. Activities are more teacher-centered so that in the learning process students only listen, do not understand Civics concepts and are less able to express ideas, and are still passive. This research is a classroom action research with qualitative and quantitative approaches consisting of 2 cycles. Each cycle consists of planning, implementing, observing, and reflecting. This research was conducted in the second semester of the 2015/2016 Academic Year. The research subjects were fourth grade students of SDN 01 Pancung Question. The results showed that the learning process using the Picture and picture model could increase student learning activities in Civics learning in class IV SDN 01 Pancung Question.  This can be seen as follows: student learning activities in the first cycle of Visual Activities obtained a percentage of 78% with a Good category (B), while in cycle 2 increased 88% with a Very Good category (SB), in cycle 1 Oral Activities obtained 76% while in cycle 2 it increased 98% with a very good category (SB), in cycle 1 Mental Activities gained 76% while in cycle 2 it increased by a percentage of 81% with a good category (B). Thus the use of the Picture and picture learning model in Civics learning in class IV can increase student learning activities.